Mental Health and Coping in the Shadow of the COVID-19 Pandemic: The Israeli Case - Mally Shechory Bitton; Avital Laufer (Frontiers Media S.A., 2021)
The COVID-19 pandemic caught the entire world off guard. Israel, similar to all other nations, was forced to cope with the unknown. "Flattening the curve" of infections has become a common term among specialists and decision makers, while explaining restricting measurements taken toward the population. Israelis, who had previously learned to deal with life under constant security threat, are now facing a new reality. The purpose of the study was to check how Israelis are psychologically affected by and coping with the COVID-19 pandemic. The study included 925 Israelis divided into three groups: ages 18-29, 30-59, and 60-88. The data were collected between March 31 and April 8, 2020, when it was already clear that this is a global plague, the country's borders were closed, and the government's directive for citizens was to remain at home while imposing limitations on the public and private sectors. The current study examined psychological distress among the three age groups as well as the associations between levels of distress, resilience, and coping strategies. Levels of distress were measured via the BSI-18 that measures anxiety, depression, and somatization. Resilience was measured using the Connor-Davidson CD-RISC scale. Coping was measured by the short version of the COPE. Psychological distress was associated with being in a younger age group, being a woman, having economic concerns, use of emotion and problem focused coping, and lower resilience. The study also found that concern for the health of family members was the strongest concern among all age groups but was highest among the younger age group. It was also found that those in the younger age group suffered from higher levels of depression, anxiety, and somatization compared to the older age group. The middle age group suffered from elevated levels of anxiety and somatization compared to the older age group. Although the older age group was the most vulnerable to the coronavirus, in this study age was found to be a protective factor from psychological distress. The results of the study suggest the need to consider the younger age group as a risk group, which hence needs to be addressed as the focus of intervention programs. It appears that the concern for their loved ones takes a heavy toll on the younger generation, and this should be considered a major source of stress.